Implementation of Hill Climbing Algorithm on Tourist Attraction Android Based Application - Shumaya Resty Ramadhani; Jan Alif Kreshna; Septian Rianda (International ABEC, 2021)
West Sumatra is one province that has been a popular destination among tourists. West Sumatra is a strategic area that holds natural beauty that is no less great, and this is evenly distributed throughout the region [1]. Data shows that the number of tourist visits continues to increase every year before the pandemic hits Indonesia. Travelers often use google maps to find routes to destinations. However, with little knowledge about the area, people only visit familiar tourist locations. Meanwhile, West Sumatra offers plenty of beautiful places. With those problems in mind, a mobile application is created to help those visitors searching the nearest tourist spots around them in real-time. Not only that, but the system also gives information about the list of places worth visiting in West Sumatra. The system implemented a hill-climbing algorithm to find the shortest path. Based on the evaluation, the application is well accepted for people who want to visit West Sumatra. 94.6% of users agree that this app is useful. The app is handy and fast enough to display the desired result to the users.